THE INFLUENCE ON SPEED ANTISTAX RESTORE FUNCTIONALITY ANIMALS AFTER INTENSE EXERCISE - A. V. Voronkov; A. A. Slietsans; N. A. Muraveva (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
A promising approach for the correction of functional disorders associated with fatigue, is the use of an-tioxidant resources, particularly flavonoids. Therefore, the aim is to study the influence of Antistax a dose of 100 mg / kg per os on the performance and portability of intense exercise in rats. Intense exercise simulated swim-ming animals with a load equal to 5% of body weight for 7 days. Physical performance was evaluated on a long voyage. Application Antistax significantly increased the efficiency of the animals after intense exercise com-pared with the control groups and the intact animal